Mapping the Balinese Social Tolerance Model (Bhinneka Tunggal Ika for Strengthening Unity in Diversity) - Japar, Muhammad; Komarudin, Komarudin; Nur Fadhillah, Dini; Syarifa, Syifa (Opción, 2019)
this article describe about social tolerance in Balinese. Although it consists of a pluralist society, Bali is one example of a symbol of tolerance in Indonesia because of a harmonious communities life. This descriptive method was con- ducted by qualitative approach that aims to describe social tolerance towards the Balinese. The result of this research shows that in Bali, there are traditions that are still obeyed and respected by all religious communities, one of them is Nyepi. Not only Hindus, all societies of Islam, Christianity, Catholicism or Confucianism also obey the rules that apply during Nyepi. Another tradition is ngejot and megibung. In the other hand, Balinese also celebrates social ac- tivities that involve all communities regardless of ethnicity or religion. They maintain the values of tolerance by respecting, caring for and not offending others, especially those related to religion.